Android-Based E-Module in Basic Culinary Arts for Vocational High School Students - Lubis, Vinny Riana; Akmal, Nikmat; Ingtyas, Fatma Tresno; Sutrisno (Jurnal Edutech Undiksha, 2024)
The challenges faced in teaching Basic Culinary Arts in vocational high schools (SMK) include the limited availability of effective learning media that can be easily accessed by students. This study aims to develop an Android-based E-Module learning media for the subject of Basic Culinary Arts, focusing on Food Processing Equipment and Food Processing Techniques, using the 4-D development model. This study is limited to three stages of the development model: Define, Design, and Development. The subjects of this study consisted of 2 content experts and 1 media expert. Data were collected using questionnaires to assess the quality of the content and media. The obtained data were analyzed using descriptive statistical techniques. The results indicate that the Android-based E-Module learning media developed has been validated by content and media experts. The content expert validation yielded a feasibility percentage of 90%, categorized as "Very Feasible," while the media expert validation showed a feasibility percentage of 94%, categorized as "Very Feasible." Based on these validation results, it can be concluded that the Android-based E-Module for Basic Culinary Arts, covering Food Processing Equipment and Food Processing Techniques, is suitable for use in the learning process.